Whither public interest: The case of Greece's public finances - Thomas Moutos; Christos Tsitsikas (Center for Economic Studies and ifo Institute (CESifo), 2010)
During the last three decades there has been an almost continuous undermining of the public interest by private interests operating either outside or inside Greek public administration. The result of this infiltration has been a gradual loss of bureaucratic autonomy to pursue the public interest. The web of relationships developed between private interests and the two dominant political parties have eroded both the efficacy of public administration and the dynamism of the private sector as incumbent firms and public (or quasi-public) sector functionaries have been using their power to prevent the birth of new firms and to raid the state coffers. The upshot of these have been the emergence of permanently large budget and current account deficits, which have in turn driven Greece's foreign indebtedness to alarming levels, necessitating the current bailout by the EU/ECB/IMF.
Keywords: E21; H11; H41; H62; H63; 330; debt; deficits; political economy; fiscal crisis; Greece; Finanzpolitik; Public Choice; Patronage; Interessenpolitik; Öffentliche Verwaltung; Öffentliches Interesse; Haushaltsdefizit; Öffentliche Schulden; Griechenland